Performance evaluation of crumb rubber modified stone mastic asphalt pavement in Malaysia - Mashaan, N.S.; Ali, A.H.; Koting, S.; Karim, M.R. (2013)
To prevent pavement distresses there are various solutions such as adopting new mix designs or utilisation of asphalt additives. The primary aim of this study was to investigate the effect of adding crumb tyre rubber as an additive to SMA mixture performance properties. This study investigated the essential aspects of modified asphalt mixtures in order to better understand the influence of CRM modifiers on volumetric, mechanical, and stiffness properties of SMA mixture. In this study, virgin bitumen 80/100 penetration grade was used, modified with crumb rubber (CRM) at five different modification levels, namely, 6, 12, 16, and 20, respectively, by weight of the bitumen. The appropriate amount of the added CRM was found to be 12 by weight of bitumen. This percentage results in the maximum level of stability. The resilient modulus (Mr) of modified SMA samples including different percentages of CRM was obviously higher in comparison with that of unmodified samples.